A Survey of Dermatophytes Isolated from Cows and Sheep in Iraq: Sudad Jasim Mohammed Mohammed K Faraj - Mohammed, Sudad Jasim (The Iraqi Journal of Veterinary Medicine, 2011)
A total of 100 animals were examined during the period of beginning of September - 2010 till the end of March 2011 at dept of Microbiology college of Veterinary Medicine Baghdad University Baghdad Iraq. These animals include 50 cow and 50 sheep. Hairs and scales were submitted to direct KOH mount smear and culture on modified Sabouraud's Dextrose agar medium The direct smear was positive in 40 ( 80%) for both cows and sheep while the growth of dermatophyte was positive in 35 ( 70%) and 38 ( 76%) for cows and sheep respectively. Species identification revealed the presence of Trichophyton rubrum ( 19 isolates ) Trichophyton verrucosum ( 10 isolates ) Trichophyton mentagrophytes ( 5 isolates ) and Microsporum canis ( one isolate ) in cow while Trichophyton rubrum (22 isolates) Trichophyton verrucosum ( 2 isolates ) and Trichophyton mentagrophytes ( 14 isolates) was recorded in sheep.